Gloss to the judgment of the Court of Appeal in Lublin of 7 July 2019, I ACa 366/19 - Bączyk, Mirosław (Studia Iuridica Toruniensia, 2023)
The problem analyzed in the commentary (gloss) concerns the possibility of access to a banking secrecy by the heirs of a bank account holder. The question is whether and to what extent the bank may disclose confidential facts to such an heir. The Court of Appeal judged that the heir may obtain information which includes confidential facts. What is more, these are not only information concerning the period after the death of the account holder, but also the entire period of the account agreement. The Author of the gloss agrees with the statement of the Court of Appeal, but he criticizes the arguments used by the Court to justify its view. He argues that in Polish doctrine and jurisprudence there is a tendency to limit heirs’ access to banking secrecy, in particular by indicating the category of facts unavailable for various periods of the bank account agreement.